Edukasi Preventif Anemia Pada Remaja Putri Berbasis Aplikasi Ceria - Aini, Efa Nur; Nian Afrian Nuari (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Anemia is a nutritional problem that is common throughout the world, not only in developing countries but also in developed countries. According to WHO, the incidence of anemia in adolescents is common in developing countries, Indonesia is a developing country. One way to prevent anemia is to use the CERIA application from the Ministry of Health. The CERIA application can monitor young women in monitoring their development and routine of taking blood supplement tablets every week. The aim of this community service is to provide preventive education based on the CERIA application in preventing anemia for young women at SMK X. The method used is the CERIA application from the Ministry of Health. The population is 21 female students consisting of representatives from each class X, XI, XII and members of the OSIS of SMK with a mean of 79.13. This means that female students experienced an increase in scores on knowledge about anemia. The results of the analysis showed that there was an increase in scores before and after being given the intervention, namely the socialization of anemia prevention in young women based on the CERIA application. It is hoped that this program will be able to prevent and manage adolescent girls who experience anemia so that the health status of adolescents can improve.